Measuring the competitiveness of tourism companies in Peru - Rivas, Cecilia (2022)
The objective of the study was to analyze the levels of competitiveness in tourism companies in Peru, the model and methodology applied by the Secretary of Tourism of Mexico in 2014 was updated, called measurement of the competitiveness of tourism service providers registered in the certifications and quality seals, derived from an exploratory and confirmatory factor analysis. A questionnaire validated and applied in the context of Peru was developed, based on which the calculation of the competitiveness index of the Peruvian tourism company was made. The results show that, overall, the performance of Peruvian tourism companies is mid-range, taking into account the average of the scores obtained in the evaluation of the seven dimensions of the model. It is concluded that there is a relationship between the high competitiveness index with categorical variables such as the size of the company, number of workers and number of years of experience of the executive in charge of its management.